2009
DOI: 10.3800/pbr.4.95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on recruitment of cyanobacteria from the sediment and bloom formation in a shallow pond

Abstract: Abstract:The initial stage of bloom formation of cyanobacteria was investigated in Hirosawa-no-ike Pond, Kyoto, Japan, from February to May 2006. This pond is prone to periodic heavey blooms of cyanobacteria from spring to autumn, despite the complete draining of water for more than two months every winter. The dominant types of cyanobacteria in the bloom were Aphanizomenon flos-aquae from February to March, followed by Microcystis spp. in April. The planktonic populations of Microcystis spp. increased continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A study by Davies et al [ 64 ] on four temperate lakes in the northwest of the USA showed that the increase in water temperature contributed to an increase in toxic Microcystis species (possessing the mcyD gene). Yamamoto [ 65 ] and Oberholster et al [ 66 ] have shown that the Microcystis species adopt survival strategies to mitigate harsh external environments such as reduced river flow, a major characteristic of the Limpopo River, by sinking into the sediments.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Davies et al [ 64 ] on four temperate lakes in the northwest of the USA showed that the increase in water temperature contributed to an increase in toxic Microcystis species (possessing the mcyD gene). Yamamoto [ 65 ] and Oberholster et al [ 66 ] have shown that the Microcystis species adopt survival strategies to mitigate harsh external environments such as reduced river flow, a major characteristic of the Limpopo River, by sinking into the sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all of the sediment is exposed to air from December to mid-February when the water is reintroduced for the new fish culture. In such a unique environment, dormant cyanobacterial colonies or resting spores are assumed to serve as inocula for the development of the bloom (Yamamoto 2009b).…”
Section: Study Sitementioning
confidence: 99%
“…[34] It also explained that Microcystis was the dominant species in the sediments in winter while in the water suspension in summer. [35] Note: The efficiency (between 90% and 110%) and slope (between −3.58 and −3.10) were satisfied for the quantification of targeting 16S and functional genes in environmental samples.…”
Section: Impact Of Temperature and Light On Cyanobacteria Recruitmentmentioning
confidence: 99%
“…During the winter, when the temperature in the Shanzi Reservoir was estimated to be 10°C, Microcystis recruitment was inhibited in the water body [40] and Microcystis mainly existed in the sediment. [35] After carbohydrate accumulation in winter, Microcystis started effective photosynthesis in late spring when the temperature is above 10°C, further leading to their dominancy in water phase. [41][42][43] Compared with previous field simulation of sediment Microcystis recruitment in Dianchi Lake [44] and Hirosawa-no-ike Pond, [45] the strong positive relationship between monthly temperature change and the concentration of Microcystis in water sample has suggested that temperature is the key environmental factor affecting Microcystis recruitment at the water-sediment interface.…”
Section: Cyanobacterial Community Structure At Water-sediment Interfacementioning
confidence: 99%